2003
DOI: 10.1046/j.1440-1827.2003.01575.x
|View full text |Cite
|
Sign up to set email alerts
|

Small cell carcinoma of the extrahepatic bile duct: Case report and immunohistochemical analysis

Abstract: A small cell carcinoma of the extrahepatic bile duct in a 75-year-old Japanese man is reported. The patient suffered from obstructive jaundice, and percutaneous transhepatic cholangiography-drainage (PTCD) revealed a massive lesion in the lower common bile duct. Because it was diagnosed as a malignant tumor, pancreaticoduodenectomy was performed. A nodular infiltrating tumor measuring 4.5 x 3.0 x 2.0 cm was located in the intrapancreatic portion of the extrahepatic bile duct. Histologically, the tumor was comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…Several cases of hepatobiliary neuroendocrine neoplasms including carcinoid tumors have been reported, but most involve hepatic carcinoids or biliary neuroendocrine neoplasms arising from or accompanying ordinary adenocarcinomas, mostly in patients with gallbladder cancer and extrahepatic CC [10][11][12][13][14]. One case of hepatic NET G1 (carcinoid tumor), but no pure biliary neuroendocrine neoplasms without ordinary CC, has been registered in our laboratories and affiliated hospitals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several cases of hepatobiliary neuroendocrine neoplasms including carcinoid tumors have been reported, but most involve hepatic carcinoids or biliary neuroendocrine neoplasms arising from or accompanying ordinary adenocarcinomas, mostly in patients with gallbladder cancer and extrahepatic CC [10][11][12][13][14]. One case of hepatic NET G1 (carcinoid tumor), but no pure biliary neuroendocrine neoplasms without ordinary CC, has been registered in our laboratories and affiliated hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…To date, several cases of hepatobiliary neuroendocrine neoplasms, mostly biliary adenocarcinomas accompanying an neuroendocrine component (MANEC), have been reported [10][11][12][13][14], but the neuroendocrine component in biliary MANEC is not well characterized. In this study, we surveyed neuroendocrine neoplasms in hepatobiliary tumors and characterized hepatobiliary MANEC.…”
Section: Introductionmentioning
confidence: 99%
“…The squamous or glandular components usually lack endocrine differentiation. According to a review of the 16 previously reported cases [1][2][3][4][5][6] and our case of small-cell carcinoma of the extrahepatic bile ducts, elder age, men, a distal site of the extrahepatic bile duct, all tend to be predominant clinicopathological features. Most of the cases showed a poor prognosis, as is the case with the small-cell carcinoma arising in the other organs.…”
Section: Discussionmentioning
confidence: 68%
“…To our knowledge, only 16 cases of primary small-cell carcinoma of the extrahepatic bile ducts have been previously reported (Table 1) [1][2][3][4][5][6]. Histopathologically, smallcell carcinoma of the extrahepatic bile duct is characterized by a diffuse proliferation of atypical small round cells with hyperchromatic nuclei and scant cytoplasm, which are also characteristics shared by small-cell lung or gastrointestinal carcinoma [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation